Terrorism in American memory : memorials, museums, and architecture in the post-9/11 era - Sturken, Marita, 1957- (New York University Press, 2022)
The role of cultural memory in American identityTerrorism in American Memory argues that the terrorist attacks of 9/11 and all that followed in its wake were the primary force shaping United States politics and culture in the post-9/11 era. Marita Sturken maintains that during the past two decades, when the country was subjected to terrorist attacks and promulgated ongoing wars of aggression, we have veered into increasingly polarized factions and been extraordinarily preoccupied with memorialization and the politics of memory. The post-9/11 era began with a hunger for memorialization and it ended with massive protests over police brutality that demanded the destruction of historical monuments honoring racist historical figures. Sturken argues that memory is both the battleground and the site for negotiations of national identity because it is a field through which the past is experienced in the present. The paradox of these last two decades is that it gave rise to an era of intensely nationalistic politics in response to global terrorism at the same time that it released the containment of the ghosts of terrorism embedded within US history. And within that disruption, new stories emerged, new memories were unearthed, and the story of the nation is being rewritten. For these reasons, this book argues that the post-9/11 era has come to an end, and we are now in a new still undefined era with new priorities and national demands. An era preoccupied with memory thus begins with the memorial projects of 9/11 and ends with the radical intervention of the National Memorial for Peace and Justice, informally known as the Lynching Memorial, in Montgomery, Alabama, a project that, unlike the nationalistic 9/11 Memorial and Museum in New York, dramatically rewrites the national script of American history. Woven within analyses of memorialization, memorials, memory museums, art projects on memory, and architectural projects is a discussion about design and architecture, the increased creation of memorials as experiences, and the role of architecture as national symbolism and renewal. Terrorism in American Memory sheds light on the struggles over who is memorialized, who is forgotten, and what that politics of memory reveals about the United States as an imaginary and a nation.